2009
DOI: 10.1073/pnas.0909176106
|View full text |Cite
|
Sign up to set email alerts
|

Inositol pyrophosphate mediated pyrophosphorylation of AP3B1 regulates HIV-1 Gag release

Abstract: High-energy inositol pyrophosphates, such as IP7 (diphosphoinositol pentakisphosphate), can directly donate a ␤-phosphate to a prephosphorylated serine residue generating pyrophosphorylated proteins. Here, we show that the ␤ subunit of AP-3, a clathrin-associated protein complex required for HIV-1 release, is a target of IP 7-mediated pyrophosphorylation. We have identified Kif3A, a motor protein of the kinesin superfamily, as an AP3B1-binding partner and demonstrate that Kif3A, like the AP-3 complex, is invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
166
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(175 citation statements)
references
References 28 publications
8
166
1
Order By: Relevance
“…Because of a preference of Vip1 to phosphorylate 5-InsP 7 to 1,5-InsP 8 , vip1D yeast cells accumulate the nonmetabolized substrate 5-InsP 7 (Azevedo et al, 2009;Onnebo and Saiardi, 2009;Padmanabhan et al, 2009) (Figure 2F). Levels of 1-InsP 7 and 1,5-InsP 8 are generally low in wild-type yeast due to the activity of Ddp1 (Safrany et al, 1998;Mulugu et al, 2007).…”
Section: Vih1 and Vih2 Complement Vip1d-but Not Kcs1d-associated Defementioning
confidence: 97%
“…Because of a preference of Vip1 to phosphorylate 5-InsP 7 to 1,5-InsP 8 , vip1D yeast cells accumulate the nonmetabolized substrate 5-InsP 7 (Azevedo et al, 2009;Onnebo and Saiardi, 2009;Padmanabhan et al, 2009) (Figure 2F). Levels of 1-InsP 7 and 1,5-InsP 8 are generally low in wild-type yeast due to the activity of Ddp1 (Safrany et al, 1998;Mulugu et al, 2007).…”
Section: Vih1 and Vih2 Complement Vip1d-but Not Kcs1d-associated Defementioning
confidence: 97%
“…The second messenger phosphatidylinositol (3,4,5)-trisphosphate (PIP 3 ), formed by the p110 family of PI3-kinases, promotes cellular growth, proliferation, and survival, in large part by activating the protein kinase Akt/PKB. We show that inositol polyphosphate multikinase (IPMK) physiologically generates PIP 3 as well as water soluble inositol phosphates.…”
mentioning
confidence: 99%
“…Inositol diphosphates, incorporating an energetic pyrophosphate bond, display numerous physiological roles, including pyrophosphorylation of a variety of protein targets (2)(3)(4). These inositol pyrophosphates are synthesized by a family of IP 6 kinase enzymes (5).…”
mentioning
confidence: 99%
“…Two studies have been published investigating how pyrophosphorylation may modulate protein activity in yeast and human cells (Azevedo et al, 2009, Szijgyrato et al, 2011 and both demonstrated that pyrophosphorylation mediates protein-protein interactions in vitro. Although no-one has yet directly demonstrated that inositol pyrophosphates can diphosphorylate proteins in vivo (Shears, 2015), perhaps model we used in this study may be useful to clarify this question, because we have demonstrated that different inositol pyrophosphates can compensate for each other and that increase in inositol pyrophosphate level will modulate S phase progression.…”
Section: Resultsmentioning
confidence: 99%